Consumer Response to Standardized Tobacco Packaging in the United Kingdom: A Synthesis of Evidence from Two Systematic Reviews - Moodie C; Angus K; Stead M (Risk Management and Healthcare Policy, 2021)
Crawford Moodie,* Kathryn Angus,* Martine Stead* Institute for Social Marketing and Health, Faculty of Health Sciences and Sport, University of Stirling, Stirling, FK9 4LA, Scotland*These authors contributed equally to this workCorrespondence: Crawford MoodieInstitute for Social Marketing and Health, Faculty of Health Sciences and Sport, University of Stirling, Stirling, FK9 4LA, ScotlandTel +44 1786 467390Email c.s.moodie@stir.ac.ukAbstract: Standardized packaging of tobacco products has now been fully implemented in 15 countries. However, there is limited evidence, apart from in Australia, on how consumers have responded to the policy. Two systematic reviews explored consumer, tobacco industry and retailer response to standardized packaging in the United Kingdom (UK), which became mandatory for cigarettes (factory-made and hand-rolled) from May 2017, following a twelve-month transition period. In the first review, electronic databases were searched for published primary research from January 2016 to February 2019. The second review used the same methods, with searches conducted between February 2019 and September 2020. The current study conducted a narrative synthesis of the findings exploring consumer response from these two systematic reviews. Eleven studies met the inclusion criteria. Studies examined consumer response to on-pack warnings (n=7 studies), appeal of packs and smoking (n=4), perceptions of harm (n=5), and behavioral responses (n=8). There was consistent evidence that standardized packaging was associated with increased warning salience and effectiveness, and reduced appeal. Findings were mixed with respect to whether standardized packs were associated with increased perceptions of harm. Standardized packaging was generally thought to deter never or occasional smokers. Standardized packaging was associated with increased thoughts of quitting during the transition period, but no study directly explored cessation or relapse prevention. Some smokers switched to cheaper cigarettes. Standardized packaging in the UK seems to be reducing the appeal of packaging and smoking and making warnings more salient, but the behavioral impact is unclear. More consumer research is needed to assess longer-term behavioral response.Keywords: cigarettes, smoking, marketing, policy, public health, review